THE INFLUENCE OF STORE IMAGE, TRUST, RISK PERCEPTION, AND BENEFIT PERCEPTION ON ONLINE MOBILE PHONE PURCHASE INTENTION - Hudawidayanti, Iis Mei; Kurniawati, Masmira (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The study intends to affect the shop image, trust, risk perception, and benefit perception of online mobile phone purchases. Methods: The Smart PLS program was used in conjunction with data acquired via a questionnaire. Because Sentra Mobile's online store is in Bibli, the population of this study includes the whole Blibli user base. In this study, non-probability sampling is used, which means that a population element has no chance of being chosen as a sample subject. Sampling is a purposeful sampling approach in which the sample is determined using multiple criteria so that it may be utilized as a sample. Results: The findings indicated that each of the variables had an impact on the purchase intention. There is a positive effect on the store's image intended for purchasing mobile phones online. Through trust mediation, store image has a higher favorable impact on the desire to buy mobile phones online. The inclination to acquire a mobile phone online is influenced positively by trust. The perception of risk has a negative effect on the inclination to acquire a mobile phone online. Conclusion and suggestion: This research can be a reference for further research related to the influence of store image, trust, perceived risk, and perceived benefits on the purchase intention of mobile phones online.